The question of morality: from Kant´s practical reason to Haberma´s discoursive ethics - Freitag, Barbara (Tempo Social, 1989)
Morality as a guiding principle for action allows for various approaches, thus suggesting an interdisciplinary treatment of the problem. This essay focus on four of such approaches: the philosophical (Kant´s), the sociological (Durkheim´s), the psychogenetic (Khlberg´s) and the discoursive (Habermas´s) ones. The cleavage that orients this selection and defines the themes for analysis is Piaget´s genetic structuralism, which provides the necessary elements to adequately grasp the problem as a whole. Genetic structuralism is based on reason, includes society in the reflexive process, recreates the genesis of judgement and considers discourse as a fundamental element. Thus Piaget finds support in Kant, takes Durkheim into account, sets the ground for Kohlberg and antecipates Haberma´s theorization.